2020
DOI: 10.1039/d0ra06256a
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur-doped activated carbon as a metal-free catalyst for acetylene hydrochlorination

Abstract: A series of sulfur-doped spherical activated carbon (SAC) catalysts were prepared with phenyl disulfide (C12H10S2) as a sulfur source for acetylene hydrochlorination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Raman spectrometry, as presented in Figure , was used to identify the structural change of carbon after sulfur doping. The intensity ratio ( I D / I G ) of amorphous carbon at 1340 cm –1 (D band) to graphite carbon at 1580 cm –1 (G band) increased slightly with increasing sulfur content, which indicated that more carbon defects were generated after sulfur doping. , The Brunauer–Emmett–Teller (BET) surface area of samples was calculated by N 2 adsorption–desorption isotherms, as shown in Figure a. The pore-size distribution was analyzed by the Barrett–Joyner–Halenda (BJH) method from the adsorption branch, as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectrometry, as presented in Figure , was used to identify the structural change of carbon after sulfur doping. The intensity ratio ( I D / I G ) of amorphous carbon at 1340 cm –1 (D band) to graphite carbon at 1580 cm –1 (G band) increased slightly with increasing sulfur content, which indicated that more carbon defects were generated after sulfur doping. , The Brunauer–Emmett–Teller (BET) surface area of samples was calculated by N 2 adsorption–desorption isotherms, as shown in Figure a. The pore-size distribution was analyzed by the Barrett–Joyner–Halenda (BJH) method from the adsorption branch, as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the C1s peak, four contributions can be deconvoluted in both samples, with the primary contribution at 284.6 eV and three declining shoulders at 285.8, 287.1, and 289.4 eV. According to the literature, the main contribution corresponds to C-C and C=C bonds, while the shoulders must be attributed to C-N or C-S at 285.8 eV, C=O at 287.1 eV, and O-C=O at 289.4 eV [45,46]. The XPS spectra of O1s were deconvoluted in three main contributions at 531.75, 533.0, and 534.5 eV.…”
Section: Evaluation Of the Surface Chemistrymentioning
confidence: 86%
“…In addition, it exhibits high catalytic activity in the hydrochlorination of acetylene [16] . As observed in the metal‐catalyzed reactions, doping with nitrogen, [17] sulfur, [18] or boron [19] is effective to increase catalytic activity.…”
Section: Synthesis Of Vinyl Chloride By Hydrochlorination Of An Acety...mentioning
confidence: 99%